2016
DOI: 10.1111/ina.12340
|View full text |Cite
|
Sign up to set email alerts
|

VOC exposures in California early childhood education environments

Abstract: Little information exists about exposures to volatile organic compounds (VOCs) in early childhood education (ECE) environments. We measured 38 VOCs in single-day air samples collected in 2010-2011 from 34 ECE facilities serving California children and evaluated potential health risks. We also examined unknown peaks in the GC/MS chromatographs for indoor samples and identified 119 of these compounds using mass spectral libraries. VOCs found in cleaning and personal care products had the highest indoor concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 34 publications
3
28
0
1
Order By: Relevance
“…As studies have shown, fragranced consumer products can be primary sources of human exposure to potentially hazardous compounds (Hoang et al 2017;Gokhale et al 2008; 3.02 × 10 7 1.12 × 10 6 2.23 × 10 6 4.01 × 10 5 3.39 × 10 7 Lost workdays (8-h equivalents) due to fragranced product exposure 1.87 × 10 8 6.42 × 10 7 1.14 × 10 7 1.79 × 10 6 2.07 × 10 8…”
Section: Resultsmentioning
confidence: 99%
“…As studies have shown, fragranced consumer products can be primary sources of human exposure to potentially hazardous compounds (Hoang et al 2017;Gokhale et al 2008; 3.02 × 10 7 1.12 × 10 6 2.23 × 10 6 4.01 × 10 5 3.39 × 10 7 Lost workdays (8-h equivalents) due to fragranced product exposure 1.87 × 10 8 6.42 × 10 7 1.14 × 10 7 1.79 × 10 6 2.07 × 10 8…”
Section: Resultsmentioning
confidence: 99%
“…The National Institute for Occupational Safety and Health has recommended an exposure level of 9.78 mg/m 3 for a short-term exposure limit of 60 minutes for adults in an occupational setting. A recent article on child care settings 53 used the California Prop 65 no significant risk level for adults and calculated a suggested no significant risk level for infants based on body weight and time spent in care settings of 0.4 mg/d, a level quickly exceeded if air levels after disinfecting approached those in the Odabasi study. 52 Lower level long-term exposure to bleach is now recognized as another cause of respiratory effects.…”
Section: Bleachmentioning
confidence: 99%
“…Much higher levels are found in a gross anatomy laboratory [29,48]; 8-h average and maximum formaldehyde levels are about 0.7 and 3 ppm, respectively [42]. Another toxic gas present in a gross anatomy laboratory is phenol [22,46], which is not only present in the embalming fluid but it is released in the early stages of human body decomposition [53]. Both NIOSH and OSHA established 5 ppm as an 8-h TLV.…”
Section: Introductionmentioning
confidence: 99%